A Single Centre Open Label Post Marketing Surveillance Study to Evaluate the Efficacy and Safety of Roop Mantra Cucumber Ayurvedic Medicinal Face Wash (International Journal of Ayurveda and Pharma Research, 2023)
The objective of the study was to assess the safety and efficacy of Roop Mantra Cucumber Ayurvedic Medicinal Face Wash in subjects with acne, facial scars, pimples, blemishes, dull skin and dry skin. Methods: This was a single-center, open-label, non-randomized post-marketing surveillance study with 120 subjects. Subjects were selected on the basis of inclusion criteria. The study included three scheduled clinical visits on days 0 (screening and baseline visit), 15 (follow-up visit), and 30 (final visit). Following an assessment of baseline data, all subjects were given Roop Mantra Cucumber Ayurvedic Medicinal Face Wash for 30 days. The efficacy of Roop Matra Cucumber Ayurvedic Medicinal Face Wash was determined by measuring changes in parameters such as skin characteristics, skin appearance, and Global Acne Assessment (GAA) score. Product safety was assessed by determining local intolerance and adverse effects of Roop Mantra Cucumber Ayurvedic Medicinal Face Wash. Results: The results of the study showed that applying Roop Mantra Cucumber Ayurvedic Medicinal Face Wash for 30 days significantly improved skin’s characteristic and appearance. Roop Mantra Cucumber Ayurvedic Medicinal Face Wash was also found to be dermatologically well tolerated and had no negative impacts over the course of the study. Conclusion: The polyherbal Roop Mantra Cucumber Ayurvedic Medicinal Face Wash was found to be very safe and effective in reducing acne, pimples, blemishes, and skin dryness with improved skin texture and appearance. Roop Mantra Cucumber Ayurvedic Medicinal Face Wash is therefore a clinically feasible and safe alternative for treating the aforementioned skin conditions.